2016
DOI: 10.1186/s13075-016-1127-6
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk of systemic sclerosis and co-aggregation of autoimmune diseases in affected families

Abstract: BackgroundSystemic sclerosis (SSc) is a rare and devastating disease affecting skin and internal organs. Familial aggregation of SSc and co-aggregation with other autoimmune diseases is rarely reported.MethodsWe identified 23,658,577 beneficiaries registered with the National Health Insurance database in 2010, 1891 of whom had SSc. We identified 21,009,551 parent–child relationships and 17,168,340 full sibling pairs. The familial risks of SSc and other autoimmune diseases and familial transmission were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…In comparison with healthy individuals, higher prevalences of autoimmune disease, such as systemic lupus erythematosus, autoimmune thyroid disease, or type 1 diabetes, have been reported concurrently in patients with IIM, as well as in first-degree relatives of both adult and juvenile patients with IIM, on the basis of data from a relatively small number of patients 5,6 . Conversely, a nationwide study in Taiwan that investigated co-aggregation of autoimmune disease in families with systemic lupus erythematosus and systemic sclerosis, identified higher relative risk of IIM than that of the general population 7,8 , and a national study in China suggested an increased risk of IIM and certain other autoimmune diseases in relatives of patients with systemic sclerosis 8 . These findings of aggregation of autoimmune diseases within families of patients with IIM suggest that shared genetic and/or environmental factors might contribute to disease risk.…”
Section: Genetic Risk Factorsmentioning
confidence: 95%
“…In comparison with healthy individuals, higher prevalences of autoimmune disease, such as systemic lupus erythematosus, autoimmune thyroid disease, or type 1 diabetes, have been reported concurrently in patients with IIM, as well as in first-degree relatives of both adult and juvenile patients with IIM, on the basis of data from a relatively small number of patients 5,6 . Conversely, a nationwide study in Taiwan that investigated co-aggregation of autoimmune disease in families with systemic lupus erythematosus and systemic sclerosis, identified higher relative risk of IIM than that of the general population 7,8 , and a national study in China suggested an increased risk of IIM and certain other autoimmune diseases in relatives of patients with systemic sclerosis 8 . These findings of aggregation of autoimmune diseases within families of patients with IIM suggest that shared genetic and/or environmental factors might contribute to disease risk.…”
Section: Genetic Risk Factorsmentioning
confidence: 95%
“…This is supported by the higher familial relative risk of the disease itself or autoimmune diseases [4, 8], low disease concordance but high concordance of autoantibodies produced in monozygotic twins [5], and multi-case SSc families that are concordant for SSc-specific autoantibodies as well as human leukocyte antigen (HLA) haplotypes [9]. Twin studies have been performed in several autoimmune diseases.…”
Section: Genetic Involvementmentioning
confidence: 99%
“…Although the exact aetiology of SLE is still unknown, both environmental and genetic factors could be involved in the development and propagation of SLE (Lo & Tsokos, ). However, the higher concordance rate in monozygotic twins and increased risk of SLE in relatives highlight the genetic factors in SLE pathogenesis (Kuo et al, ). Various genes have been suggested as SLE predisposing factors which are commonly known as “ SLE susceptibility genes” such as human leucocyte antigen (HLA) (Armstrong et al, ), mannose‐binding lectin (MBL) (Tanha et al, ), Fc gamma receptor (FcγR) (Tsang‐A‐Sjoe et al, ) and programmed cell death‐1 (PD‐1) (Gianchecchi, Delfino, & Fierabracci, ).…”
Section: Introductionmentioning
confidence: 99%